Determinants of property sector profitability: Empirical evidence from the selected publicly listed real estate companies in the ASEAN-5 - Palileo, France Gabriel D. (Animo Repository, 2023)
Using quarterly data from 10 real estate firms listed on the Property Sector of each country's respective stock exchanges from 2018 to 2021, this pioneering study examined the relationship between GDP Growth Rate, Inflation Rate, Interest rate, and Exchange Rate; and the profitability, as measured by the Return on Assets (ROA), of real estate companies in the ASEAN-5 nations of the Philippines, Indonesia, Malaysia, Thailand, and Vietnam. This paper also examined COVID’s moderating effect on the aforementioned macroeconomic variables. Panel GMM Model and Granger Causality Method were the study's two primary statistical approaches employed to generate the conclusion. Results showed that only GDP, Inflation, and Exchange Rate have a Granger Causal relationship with profitability. Furthermore, COVID Wave 2 only moderated the impact of inflation on profitability. Generally, however, the property sector exhibited strong resilience, even with the threat of the virus, evidenced by the stable ROA values all throughout the observed period, and the insignificant impact of COVID Wave 2 alone. This paper offers strong implications for the property sector, and would help investors in formulating strategic ways to safeguard its profits and adapt to the changing business landscape, allowing them to plan and alter risk-management and cost-optimization strategies; and for the government institutions and financial regulators in policy-making decisions.